Behavioral Aspects in the Planning and Budget Process in the Healthy House Inpatition Clinic Baznas Al Chusnaini Sidoarjo - Ervinda Dwi; Sri Trisnaningsih (International Journal of Management Research and Economics, 2024)
Baznas Al Chusnaini Sidoarjo Healthy Home Inpatient Clinic is a Public Non-Profit Organization that provides services to the community, especially the poor.This research aims to find out how the budget preparation process works at the Baznas Al Chusnaini Sidoarjo Healthy Home Inpatient Clinic and find outbehavioral aspects in the planning and budgeting process. The methodological approach used is case study analysis. This analysis was identified as gaining an in-depth understanding of behavioral aspects in the planning and budgeting process at the Baznas Al Chusnaini Sidoarjo Healthy Home Inpatient Clinic. Data collection techniques use interviews. They implement a budget preparation process involving participation from management and the medical services division, increasing responsibility for the budget prepared. A mixed top-down and bottom-up approach is used in budgeting, where the clinic starts from the top level of the organization and then supplements with lower level employees. The budget preparation process involves 4 stages: preparation, ratification, implementation, and reporting and evaluation. This article highlights the importance of the involvement of all parties in budgeting to achieve shared responsibility and success in the delivery of public non-profit health services. The implementation of the theory of budgeting behavior in Healthy Homes is in accordance with the core of the theory. As a suggestion, Baznas Al Chusnaini Sidoarjo Healthy Home Clinic is advised to maintain the budgeting aspect by integrating participatory processes, ensuring the involvement of all related parties, as well as carrying out evaluations and updates to maintain the relevance of the budget to the goals and needs of the organization.